Biocontrol of invasive pheretimoid earthworms using Beauveria bassiana - Nouri-Aiin, Maryam (PeerJ, 2021)
BACKGROUND: Invasive species cause enormous costs of over $120 billion to the U.S. economy. Among biological invasions, the invasion by pheretimoid earthworms has gone relatively unnoticed and their invasion imposes yet unknown damage on USA agriculture and horticulture. The main dispersal is with horticultural goods such as plant material and composts. Pheretimoids affect commercially important hardwood forest. With no chemical agents currently certified for earthworm control nor any best horticultural practices, slowing the invasion is difficult. METHODS: In this study we measured the efficacy of a commercial entomopathogenic fungal isolate of B. bassiana (BotaniGard(®)) to kill pheretimoid earthworms under greenhouse conditions. Four treatments of B. bassiana were applied: The commercial product as per label, re-cultured commercial B. bassiana, 15 g and 25 g millet grains mycotized with recultured product. In all, three bioassays were conducted in 2 consecutive years with two batches of BotaniGard(®). RESULTS: With fresh batches, all B. bassiana treatments with re-cultured product resulted in greater than 70% mortality within 4 weeks. Mortality was less than 60% when BotaniGard(®) was used as prescribed by the label. When using 1-year old spores (refrigerated at 4 °C), mortality rates for B. bassiana treatments were less than 20% and not significantly different from the controls. However, B. bassiana still affected the earthworms by slowing their development from juvenile to adult stage. CONCLUSION: B. bassiana was effective against pheretimoid earthworms. Overall, mycotized millet grains did not significantly increase mortality over the re-cultured, directly applied B. bassiana spores. More experimentation is needed to find the mode of action of the re-cultured B. bassiana before investigating ways to improve the efficacy of B. bassiana when applied as prescribed on the label.